Impact of a Cryptococcal meningitis diagnosis and treatment program at Lira Regional Referral Hospital in rural, Northern Uganda - Abigail Link; Mark Okwir; David Meya; Betty Nabongo; James Okello; Danuta Kasprzyk; Paul R. Bohjanen (Public Library of Science (PLoS), 2022)
In rural areas of sub-Saharan Africa, infrastructure and resources for treatment of cryptococcal meningitis (CM) are often lacking. We introduced a CM diagnosis and treatment program (CM-DTP) at Lira Regional Referral Hospital (LRRH) in rural Uganda to determine if implementing high-quality standard of care protocols would improve outcomes. Information extracted from hospital charts and clinical record forms at LRRH were used to compare diagnoses, treatments, and outcomes for all patients diagnosed with meningitis (n = 281) over a two-year period after initiation of the CM-DTP in February of 2017 to all patients diagnosed with meningitis (n = 215) in the two preceding years. After implementation of the CM-DTP, we observed increased confirmed diagnoses of CM from 22.2% (48 of 215) to 35.2% (99 of 281), (p = 0.002) among all patients diagnosed with meningitis. Among all patients treated for CM, the proportion who received standard of care treatment with amphotericin B plus fluconazole increased from 63 of 127 (49.6%) to 109 of 146 (74.7%), (p <0.001) and mortality improved from 66 of 127 (52.0%) to 57 of 146 (39.0%), (p = 0.04) after implementation of the CM-DTP. Implementation of the CM-DTP was associated with increased number of lumbar punctures and decreased use of antibiotics in patients with CM, as well as decreased mortality among patients with meningitis from all causes. Improved diagnosis, treatment, and mortality were observed following implementation of the CM-DTP. Our results demonstrate that quality treatment of CM in rural Uganda is feasible.